(untitled) (GIST – Education and Learning Research Journal, 2016)
This action research study explored the effects of an intervention linking both culture and citizenship in a tenth-grade English language class, and aimed at finding evidence of intercultural communicative competence (ICC) skills through the writing of narrative texts in English. Participants were 75 tenth-grade students, between the ages of 14 and 17 years old who attended three different public schools in Bogotá, Colombia. Through literature circles (discussion groups) and storytelling tools, learners played an active role, discovered similarities and differences among cultures, reflected upon their tolerance levels, and explored ways to face problems. Findings suggest that students were able to identify differences in cultures and how those differences helped them to build identity. In addition, they analyzed how they reacted in situations where their tolerance skills were challenged.